Pengaruh Pertumbuhan Aktiva Produktif, Dana Pihak Ketiga dan Ukuran Perusahaan Terhadap Profitabilitas Lembaga Perkreditan Desa (LPD) di Kecamatan Mengwi - Ni Komang Mela Tri Utari; I Made Sara; Ni Putu Rediatni Giri (Warmadewa Economic Development Journal (WEDJ), 2019)
This study aims to determine the effect of earning assets, third party funds and company size on LPD profitability in Mengwi District from 2015-2017. The number of Village Credit Institutions (LPDs) which were sampled were 37 LPDs using 3 years of observation, so that 111 observation samples were obtained. The data analysis technique used in this study is multiple linear analysis techniques which are processed using the SPSS program. The results of this study use two stages, the first stage with a total sample of 111 but the data are not normally distributed, there is autocorrelation and heterocedasticity, so the data is released so that no symptoms occur so that the data amounts to 44. The second stage shows the results of the negative asset variable significant to LPD profitability with t count value of -0.025 and significance level of 0.000, third party fund variables have a positive and insignificant effect on LPD profitability with t count value of 0.005 and significance level of 0.194 and firm size variables have a significant positive effect on LPD profitability with the value of t count is 0.002 and the significance level is 0.001.